Aflatoxin B1-Induced Neurobehavioral Alterations in Chickens: Inhibition of Brain Acetylcholinesterase Activity, Induction of Oxidative Stress, and Promotion of Inflammatory Gene Expression - Wisam Hussein Selman; Noora Kadhim Hadi Alyasari; Hassan Al-Karagoly (Stresses, 2025)
Aflatoxin B1 (AFB1), a potent mycotoxin, poses a significant threat to animal health through contaminated feed. Our study aims to investigate the neurotoxic effects of AFB1in chickens, with a special emphasis on the brain. Seven-day-old chickens were fed AFB1-contaminated feed (5 mg of AFB1/kg of feed) for two weeks, after which neurobehavioral assessments and biochemical analyses were conducted and compared to control chickens. In the open-field test, chickens exposed to AFB1 exhibited a reduction in locomotor activity and exploratory behavior. Additionally, AFB1 exposure increased the tonic immobility response. Biochemical analyses revealed that AFB1-contaminated feed reduced whole-brain acetylcholinesterase activity, suggesting impaired cholinergic neurotransmission. Indicators of oxidative stress in the brain revealed a reduction in glutathione levels, superoxide dismutase levels, and total antioxidant capacity, alongside an increase in malondialdehyde levels, indicating heightened oxidative stress in the brain. The neurotoxic effects of AFB1 were further supported by the upregulation of pro-inflammatory cytokine genes, including interleukin-1 beta, interleukin-6, interleukin-17, and inducible nitric oxide synthase, as determined by real-time quantitative polymerase chain reaction. Our study demonstrates that AFB1-contaminated feed influences chicken neurobehavioral outcomes and brain biochemistry and represents the inaugural evidence that AFB1 exposure markedly reduces AChE activity in the whole brain of chickens.